PERBANDINGAN KUAT TEKAN BATA PLASTIK BERJENIS POLYPROPYLENE (PP) POLYETHYLENE TEREPHTHALATE (PET) DAN HIGH DENSITY POLYETHYLENE (HDPE) - Muhammad Ridho Reksi; Dian Rahayu Jati; Yulisa Fitrianingsih (Jurnal Teknologi Lingkungan Lahan Basah, 2021)
AbstractPlastic waste needs attention because it can cause serious problems if not managed properly. Of the various types of plastics, the most widely disposed of to the environment are Polypropylene, Polyethylene Terephthalate, and High-Density Polyethylene which are usually in the form of plastic bags and bottles. This research was conducted to make bricks made of plastic as an alternative material for infrastructure that is economical, strong, and durable, which is seen based on the compressive strength value based on its type, namely PP, PET, and HDPE plastic bricks. The compressive strength testing phase is carried out three times in each type. The selling price of plastic bricks is determined by the Markup pricing method. The process of plastic brick making includes collecting plastic waste, washing, drying, chopping, melting, and printing. Based on the research results, the plastic bricks produced from the types of PET, HDPE, and PP are in the form of blocks with a size of 19 cm x 10 cm x 6.5 cm, where the PET type brick requires 5.1 kg of waste, 3.6 kg of HDPE type, and the type of PP as much as 3 kg. The compressive strength test values for PP, PET, and HDPE plastic bricks have met the compressive strength standards based on SNI 15-2094-2000, with the highest average compressive strength test values found in PP plastic bricks of 246 kg/cm², plastic bricks HDPE type 166 kg/cm², and plastic brick type PET 98.7 kg/cm². The selling price of plastic bricks without including the purchase price of plastic as raw material for making plastic bricks (Scenario I) for PP plastic bricks costs Rp1.907,00/brick, PET types Rp3.024,00/brick, and HDPE types Rp3.464,00/brick. While the selling price of plastic bricks by entering the purchase price of plastic as raw material for making plastic bricks (Scenario II) for PP plastic bricks Rp2.867,00/brick, PET type Rp4.624,00/brick, and HDPE type Rp3.944,00/brick.Keywords: Compressive Strength, Markup Pricing, Plastic Brick. AbstrakSampah plastik perlu mendapatkan perhatian karena menimbulkan masalah yang serius jika tidak dikelola dengan baik. Dari berbagai jenis plastik, yang paling banyak dibuang ke lingkungan adalah jenis Polypropylene, Polyethylene Terephthalate, dan High Density Polyethylene yang biasanya dalam bentuk kantong dan botol plastik. Penelitian ini dilakukan guna membuat bata berbahan plastik sebagai bahan alternatif infrastruktur yang bersifat ekonomis, kuat dan tahan lama yang dilihat berdasarkan nilai kuat tekan berdasarkan jenisnya, yaitu bata plastik jenis PP, PET, dan HDPE. Tahap pengujian kuat tekan dilakukan sebanyak tiga kali pengulangan di setiap jenisnya. Harga jual bata plastik ditentukan dengan metode Markup pricing. Proses pembuatan bata plastik yaitu pengumpulan sampah plastik, pencucian, penjemuran, pencacahan, pelelehan, dan pencetakan. Berdasarkan hasil penelitian, bata plastik yang dihasilkan dari jenis PET, HDPE, dan PP berbentuk balok dengan ukuran 19 cm x 10 cm x 6,5 cm, dimana bata jenis PET memerlukan sampah sebanyak 5,1 kg, jenis HDPE sebanyak 3,6 kg, dan  jenis PP sebanyak 3 kg. Nilai uji kuat tekan pada bata plastik jenis PP, PET, dan HDPE telah memenuhi standar kuat tekan berdasarkan SNI 15-2094-2000, dengan nilai uji kuat tekan rata-rata tertinggi terdapat pada bata plastik jenis PP sebesar 246 kg/cm², bata plastik jenis HDPE 166 kg/cm², dan bata plastik jenis PET 98,7 kg/cm². Harga jual bata plastik tanpa memasukkan harga beli plastik sebagai bahan baku pembuatan bata plastik (Skenario I) pada bata plastik jenis PP seharga Rp1.907,00/bata, jenis PET Rp3.024,00/bata, dan jenis HDPE Rp3.464,00/bata. Sedangkan harga jual bata plastik dengan memasukkan harga beli plastik sebagai bahan baku pembuatan bata plastik (Skenario II) pada bata plastik jenis PP Rp2.867,00/bata, jenis PET Rp4.624,00/bata, dan jenis HDPE Rp3.944,00/bata.Kata Kunci: Bata Plastik, Kuat Tekan, Markup Pricing.